Product Design for Utilizing Waste Husk in Ciwulan Village into Rice Husk Brickets Using the Taguchi Method - Hakim, Arif Rahman; Suryapranatha, Dicky; Amalia; Hakim, Afif (Journal of Advances in Information and Industrial Technology, 2024)
The village of Ciwulan faces environmental challenges due to the abundance of rice husk waste. This study investigates the Taguchi method for converting rice husk waste into briquettes to improve production quality and efficiency. By evaluating the impact of rice husk charcoal, adhesive, and drying time, the study identifies the optimal combination to enhance combustion efficiency. The experimental results indicate that drying time significantly influences briquette quality, with the optimal combination being 100 grams of rice husk charcoal, 100 grams of adhesive, and 48 hours of drying. This combination resulted in the lowest average burning time of 9.5 minutes compared to other combinations. Using the Taguchi method effectively reduced burning time provided a practical solution for managing rice husk waste, and improved the quality of eco-friendly renewable energy products. This study offers a novel approach to agricultural waste processing with potential economic benefits for rural communities.